Tasks of a nurse in the care of a patient with urolithiasis treated with percutaneous nephrolithotripsy - Weronika Nawłatyna; Paulina Myszka; Piotr Pawłowski; Katarzyna Bujak; Klaudia Olga Jakubowska; Aneta Kościołek; Violetta Mianowana (Kazimierz Wielki University, 2019)
Introduction. Contemporarily urolithiasis is a serious problem in nephrology. This disease is conditioned by many factors, including climatic, geographical, ethnic and genetic. The most important ones, however, include diet and the composition of urine excreted. Urolithiasis can be symptomatic and asymptomatic. There are many methods of its treatment. The most commonly used methods are pharmacological and surgical ones, and modern treatment methods are also on their increase. Untreated urolithiasis can lead to many complications. Aim. The aim of the study was to determine the tasks of a nurse in the care of a patient with urolithiasis treated with percutaneous nephrolithotripsy. Methods and materials. The individual case method was used in the study, using the following research techniques: nursing interview, observation, measurement and documentation analysis. The research tools used for the study include the Individual Nursing Care Card, the Visual Analogue Scale - VAS, risk of postoperative nausea and vomiting- the Apfel score. Findings. Nine nursing diagnoses based on the patient's health issues were made during the study process. Conclusions. The nursing problems concerning the patient result from surgery and hospitalization.